2012
DOI: 10.3389/fncir.2012.00058
|View full text |Cite
|
Sign up to set email alerts
|

From behavioral context to receptors: serotonergic modulatory pathways in the IC

Abstract: In addition to ascending, descending, and lateral auditory projections, inputs extrinsic to the auditory system also influence neural processing in the inferior colliculus (IC). These types of inputs often have an important role in signaling salient factors such as behavioral context or internal state. One route for such extrinsic information is through centralized neuromodulatory networks like the serotonergic system. Serotonergic inputs to the IC originate from centralized raphe nuclei, release serotonin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 182 publications
(293 reference statements)
2
46
0
Order By: Relevance
“…In multiple brain areas, serotonergic fluctuations reflect shifts in social context (Hall et al 2011;Mas et al 1995;Nakazato 2013;Watt et al 2007). Serotonin is also a strong modulator of sensory responses to incoming social stimuli (Deemyad et al 2013;Hurley and Sullivan 2012). The social responsiveness of the serotonergic system thus has a potentially important role in sensory processing during conspecific interaction.…”
mentioning
confidence: 99%
“…In multiple brain areas, serotonergic fluctuations reflect shifts in social context (Hall et al 2011;Mas et al 1995;Nakazato 2013;Watt et al 2007). Serotonin is also a strong modulator of sensory responses to incoming social stimuli (Deemyad et al 2013;Hurley and Sullivan 2012). The social responsiveness of the serotonergic system thus has a potentially important role in sensory processing during conspecific interaction.…”
mentioning
confidence: 99%
“…This is, for example, the case for the midbrain TSd. Both cholinergic and serotonergic inputs are likely to have qualitatively different effects on different cell types in the TSd based on studies performed in other midbrain structures (Hurley et al, 2004;Hurley and Sullivan, 2012). Knowledge of the behavioural contexts and stimulus features that reliably activate serotonergic and cholinergic inputs to the ELL as well as other electrosensory structures will be essential for developing a functional theory of neuromodulation of sensory processing.…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has been made in unravelling the relationships between the effects of neuromodulators at the cellular and at the systems level, i.e. the processing of sensory stimuli and its consequences for behaviour (for reviews, see Birmingham and Tauck, 2003;Edeline, 2012;Hurley et al, 2004;Hurley and Sullivan, 2012;Witkovsky, 2004). For example, at the single-cell level, neuromodulators have been implicated in facilitation of evoked responses, increases in signal-to-noise ratio, and improved functional properties of sensory neurons in the visual, auditory and somatosensory systems (for reviews, see Edeline, 2012;Hurley et al, 2004;Hurley and Sullivan, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, animal studies have demonstrated that serotonin alters multiple aspects of the neural response to sound. Not only does it change the number of spikes evoked by auditory stimuli Pollak, 1999, 2001), but also the latency and precision of initial spikes and the timing of spike trains and therefore all response properties contributing to the encoding of sensory stimuli (Hurley and Pollak, 2005). As the serotonin transporter [5-HT transporter (5-HTT)] is considered to be crucial for the regulation of serotonin availability and a common functional polymorphism has been identified in the serotonin transporter gene (SLC6A4; Heils et al, 1996), we hypothesized that it might be implicated in subcortical auditory processing.…”
Section: Introductionmentioning
confidence: 99%